Família acolhedora: contribuições de Winnicott sobre a importância do ambiente familiar para o desenvolvimento infantil - Olic, Tatiana Bacic (2019)
The purpose of this paper is to understand how the foster family can facilitate the process of maturation and development of the child that needs to be removed from the relationship with their family of origin. For this I make a dialogue between the Winnicottian theory and this service of the public policy of social assistance, in order to help in the discussion of the importance of the environment for the promotion of child development. The changes in the conception of the family and the recognition of their role in the formation and integral development of the individual made the state and the society transform the way they look into it and also changed the actions in relation to the protection of the childhood. This was done by the revision of the care model in cases of children who are away from family life, the structuring policies to support families, and the advancement of rights, which places the family at the center of the policy and creates alternatives to take care of children and adolescents, seeking a new practice that provides the best development in this important phase of life. In this specific sense the welcoming family offers what is necessary to the child in the period of remoteness of his family, allowing the continuity of its development, since it provides continuous and individualized care, in an environment of support and with reference figures. Another aspect reflected in the research is based on Winnicott's theoretical foundation based on his Theory of Maturity, pointing out the environment as crucial for the development and maturation of the individual, indicating the impact that the separation from family life may have on the development and future personality of the individual. For Winnicott, the environmental stability and continuity of care offered in the early years of a child's life are important to underpin the basis of mental health. The reflections made in this dissertation, together with the experiences brought by the foster families in the conducted interviews and the care offered by the service team, form a caring network capable of impacting positively in development of children, confirming the importance of a suitable environment for the infant development, especially in early life